Chromium supplementation: A tool for alleviation of thermal stress in poultry - Şahin, Kazım; Tuzcu, M.; Smith, M.O.; Şahin, Nurhan. (My University, 2009)
Thermal stress is one of the major causes leading to loss of production and profit in the poultry industry. Productivity in general and feed efficiency, nutrient utilization, growth rate, egg production and egg quality, in particular, are depressed as a result of thermal stress. Thermal temperature also adversely affects availability of minerals (e.g. zinc (Zn), chromium (Cr) and selenium (Se)), suggesting that increased mineral excretion and decreased mineral retention are also other important consequences of thermal stress. Moreover, thermal stress leads to oxidative stress, inflammation and reduced antioxidant status of the bird in vivo, resulting in oxidative damage and decreased plasma concentrations of minerals (e.g. Zn and Cr) and vitamins (e.g. vitamin C and vitamin E). Chromium is a well-known essential trace element for animals. It appears to have a beneficial role in the regulation of insulin's action on carbohydrate, protein and lipid metabolism. Chromium is a part of glucose tolerance factor and chromodulin. In addition, Cr is thought to be essential for activating certain enzymes and for stabilization of proteins and nucleic acids. Chromium is postulated to function as an antioxidant. Some factors such as stress, high carbohydrate intake, obesity and acute exercise cause Cr depletion. Chromium deficiency causes disruption in carbohydrate and protein metabolism, reduction in insulin sensitivity in peripheral tissues, as well as impairment in growth rate. Chromium is used in the diets of thermal-stressed poultry because of its reported benefits. Chromium supplementation may decrease levels of blood corticosterone, glucose, inflammation and oxidative stress markers and increase weight gain in thermal-stressed poultry. Dietary intake of Cr may also improve the metabolizability of organic nutrients, retention of trace elements and meat quality in thermal-stressed poultry. This review deals with the effects of dietary Cr supplementation in poultry reared under thermal stress. © CAB International 2009.
Keywords: Chromium; Poultry; Stress